Pengaruh Aplikasi Poro Belajar Bahasa Jepang Kanji terhadapKemampuan Kanji pada Mahasiswa Prodi Pendidikan Bahasa Jepang FKIP Universitas Riau - Ramadhany; Merri Silvia Basri; Adisthi Martha Yohani (Universitas Cokroaminoto Palopo, 2022)
Learning media is one of the supporting components that can help a learning process. One of the learning media that can be applied is the application media in learning kanji. The application is called